Comparative study of linear and curvilinear ultrasound probes to assess quadriceps rectus femoris muscle mass in healthy subjects and in patients with chronic respiratory disease. Issue 1 (12th January 2016) - Mandal, S; Suh, E; Thompson, A; Connolly, B; Ramsay, M; Harding, R; Puthucheary, Z; Moxham, J; Hart, N
Abstract : Introduction: Ultrasound measurements of rectus femoris cross-sectional area (RFCSA ) are clinically useful measurements in chronic obstructive pulmonary disease (COPD) and critically ill patients. Technical considerations as to the type of probe used, which affects image resolution, have limited widespread clinical application. We hypothesised that measurement of RFCSA would be similar with linear and curvilinear probes. Methods: Four studies were performed to compare the use of the curvilinear probe in measuring RFCSA . Study 1 investigated agreement of RFCSA measurements using linear and curvilinear probes in healthy subjects, and in patients with chronic respiratory disease. Study 2 investigated the intra-rater and inter-rater agreement using the curvilinear probe. Study 3 investigated the agreement of RFCSA measured from whole and spliced images using the linear probe. Study 4 investigated the applicability of ultrasound in measuring RFCSA during the acute and recovery phases of an exacerbation of COPD. Results: Study 1 showed demonstrated no difference in the measurement of RFCSA using the curvilinear and linear probes (308±104 mm 2 vs 320±117 mm 2, p=0.80; intraclass correlation coefficient (ICC)>0.97). Study 2 demonstrated high intra-rater and inter-rater reliability of RFCSA measurement with ICC>0.95 for both. Study 3 showed that the spliced image from the linear probe was similar to the whole image RFCSA (308±103.5 vs 263±147 mm 2, p=0.34; ICC>0.98). Study 4 confirmed the clinical acceptability of using the curvilinear probe during an exacerbation of COPD. There were relationships observed between admission RFCSA and body mass index (r=+0.65, p=0.018), and between RFCSA at admission and physical activity levels at 4 weeks post-hospital discharge (r=+0.75, p=0.006). Conclusions: These studies have demonstrated that clinicians can employ whole and spliced images from the linear probe or use images from the curvilinear probe, to measure RFCSA . This will extend the clinical applicability of ultrasound in the measurement of muscle mass in all patient groups.